Behavior of child droplets during micro-explosion and puffing of suspension fuel droplets: The impact of the component mixing sequence. (15th November 2022) - Antonov, D.V.; Voytkov, I.S.; Strizhak, P.A.
Highlights: Liquids mixing sequence affects the composition of child droplets. Child droplets from micro-explosion and puffing are significantly different. Differences in child droplets with and without carbon particles were discovered. Child droplets with combustible and noncombustible components were determined. Correlations between the fragmentation delay time and the child droplets were shown. Abstract: The article provides experimental research findings on the behavior of micro-explosion and puffing of two-liquid droplets in different droplet formation schemes: liquid combustible component (rapeseed oil) as the shell with liquid incombustible component (water) as the core and vice versa. The experiments were conducted on fuel compositions that had not been pre-mixed; no coal particles had been added into them. These conditions aimed to reflect industrial production conditions with separate injection and blow-in of components into combustion chambers. Shadow Photography and Planar Laser Induced Fluorescence techniques were used in the experiments. An alcohol burner was used for heating droplets. The temperature of the heating medium was varied in the range of 850–1050 K by adjusting the vertical distance of the droplet from the burner bottom to match the conditions typical for industrial applications, specifically, composite fuel creation technologies and thermal/flame purification of liquids. Conditions have been determined under which droplets of combustible and non-combustible components are atomized during fragmentation thus producing polydisperse and monodisperse aerosols. Effects have been discovered whereby the fragmentation of combustible and noncombustible liquid components produces droplets of different sizes. Correlations between the size and component composition of child droplets with the heating temperature and mixing sequence of the liquids in the parent droplet have been established. Graphical abstract: Image, graphical abstract